1986
DOI: 10.1590/s0074-02761986000200012
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and survival of Biomphalaria Glabrata deprived of water

Abstract: Immature and mature Biomphalaria glabrata are kept out of water at relative humidities varying from 0 to 100%. When snails are submitted to a saturated atmosphere, they show a slow weight loss and survival may be long. If relative humidity (RH) decreases, weight loss becomes important and survival is short. A reduced RH (0 to 65%) produces similar effects. During desiccation, fasting has no noticeable effect; survival depends essentially on weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…IE snails lost more weight during the experimental period than did IS snails; the increased weight loss in IE snails was probably due to loss of water, as reported previously (von Brand et al, 1957;Vianey-Liaud andLancastre, 1986a, 1986b) for aestivated B. glabrata snails.…”
Section: Discussionsupporting
confidence: 81%
“…IE snails lost more weight during the experimental period than did IS snails; the increased weight loss in IE snails was probably due to loss of water, as reported previously (von Brand et al, 1957;Vianey-Liaud andLancastre, 1986a, 1986b) for aestivated B. glabrata snails.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, previous experiments had shown that this value is close to the extreme resistance of snails submitted to constant hunger (group 6 in the present paper) when they are reared in water (von Brand et al, 1957;Vianey-Liaud, 1984, 1990Vianey-Liaud & Lancastre, 1986). …”
Section: Discussionsupporting
confidence: 82%
“…It is known that freshwater snails of the genus Biomphalaria, intermediate hosts of Schistosoma mansoni, are tolerant to anoxia exposure, starvation, and desiccation/estivation (Richards 1967;Sturrock 1970;Vianey-Liaud and Lancastre 1986;Teles and Marques 1989;Ohlweiler and Kawano 2001). Other studies have also described the metabolic adjustments that are made under these conditions (Becker 1983;Patience et al 1983;Meyer et al 1986;Wolmarans 1987;Thompson and Mejiascales 1993;Bezerra et al 1999).…”
Section: Introductionmentioning
confidence: 99%